Pengenalan Dan Penggunaan Aplikasi WPS Presentation Pada CV. Bintang Angkasa - Ria Eka Sari; Alfa Saleh; Heri Gunawan; Ahir Yugo Nugroho; Siti Nur Zahro’a (Jurnal TUNAS, 2022)
Applications for making presentations have actually existed since the launch of a GUI (Graphical User Interface) based operating system, namely Windows. The operating system packages and office application packages issued by Microsoft Corporation do not have significant weaknesses, only the high prices for each package. One of these reasons is the trend of using pirated software to develop, especially in Indonesia. In addition to violating the law, the use of pirated applications can cause work delays, especially administrative work. Microsoft Powerpoint applications that are used today are paid software. So why don't we use free or free applications to support our daily work activities? The application referred to here is an application for presentations, namely WPS Presentation, which is an open-source license agreement that makes it easy for us to get the software package. Thus the question arises, why don't we migrate to WPS presentations to help us design, build, and package our projects to make them more attractive. Many reasons that users put forward in terms of company staff are that they are used to the old one, and don't want to bother using the new one anymore.